Landscape evolution and preservation of ice over one million years old quantified with cosmogenic nuclides 26Al, 10Be, and 21Ne, Ong Valley, Antarctica - Bibby, Theodore C. (UND Scholarly Commons, 2014)
Antarctica has been glaciated for the past 35-40 million years (Denton et al., 1991) and evidence of periodic fluctuations of the Antarctic ice sheet (AIS) during the Cenozoic are recorded in the ice sheet itself, deep sea sediments, and glacial deposits on the continent (Ingólfsson, 2004). Quaternary continental records of AIS extent is limited to few locations along the Transantarctic Mountains (TAM) and coastal continental boundaries (Denton et al., 1984; Denton et al., 1989). Records of atmospheric variation over time, glacial extents, and ice sheet responses to environmental changes are required to understand modern day forces on climate and the environment and provide a context in which to relate modern observations to the past. In this framework, this paper evaluates the geomorphic stability of Ong Valley within the Central Transantarctic Mountains (CTM) and the preservation of Pleistocene aged ice underneath an insulating lag deposit. Ong Valley in the Central Transantarctic Mountains (CTM) contains ancient buried glacier ice derived from past flow of the adjacent Argosy Glacier. The valley floor is covered with patterned ground and has three distinct glacial tills. Geomorphic and stratigraphic evidence shows that these deposits originate from sublimation of debris-laden glacier ice. Buried glacier ice is still present beneath the youngest two drifts, one of which is older than one million years. The tills above the ice record the repeated advances and stagnations of the Argosy Glacier. Cosmogenic exposure age dating of these tills provides ages, ice sublimation rates and regolith erosion rates that support the antiquity of the ice below. The oldest ice on Earth has an undisputed age of 800 Kya and is at the bottom of large ice sheets (Fischer et al., 2013). Access to it requires extensive drilling through kilometers of ice. Conversely, the ice in Ong valley is preserved beneath only 1 m of till and is over 1 million years old. Geomorphically similar ice was found in Beacon Valley, but its age (~8.1 Mya) ...